Embracing Diversity: The Dual Role of Gay-Straight Alliances - Stonefish, Twiladawn; Lafreniere, Kathryn D. (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
The social landscape has changed regarding public knowledge, perception, and acceptance of “alternative” sexual lifestyles. In recent years, public and political discourse around issues of non-heterosexual orientations has shifted significantly. Despite many legal milestones, society has not realized complete inclusion of individuals whose sexual orientations do not conform to the mainstream, heterosexual majority. Non-heterosexual Canadians still experience negative repercussions of heterosexism in both social and institutional realms. This article discusses one important avenue of advocacy—gay–straight alliances—and takes the position that these alliances serve a dual role: education and social activism.